DAMPAK KONTROL FREKUENSI PENGALAMAN PELAYANAN PADA HUBUNGAN ANTARA KOMPETENSI DENGAN KINERJA PELAYANAN MUTASI PEGAWAI PUBLIK - Afred Suci (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. This study aims to examine the relationship between employee‟s competencyand mutation-related service performance by controling the frequency of mutationrelatedexperience in public employees. Data were collected with accidental samplingtechnique on 90 Riau Province public employees who was having their mutation papersprocessed. Hypotheses tested by employing descriptive statistic, rank-Spearmancorrelation and partial correlation with controling factor. The descriptive test resultindicates that employee‟s competency and their service performance related to mutationis still unsatisfied. The Spearman test result proves the strong and positive relationshipbetween employee‟s competency and mutation-related service performance.Meanwhile, partial correlation with controling factor test result reveals the enhance ofemployee‟s competency and mutation-related service performance relationship aftercontroled by the frequency of mutation-related experience.